Roles of N6-Methyladenosine (m6A) in Stem Cell Fate Decisions and Early Embryonic Development in Mammals - Zhang, Meng; Zhai, Yanhui; Zhang, Sheng; Dai, Xiangpeng; Li, Ziyi (Frontiers in Cell and Developmental Biology, 2020)
N6-methyladenosine (m6A) is one of the most abundant and internal mRNA modifications that affects multiple biological processes in eukaryotic mRNA. The majority of m6A sites are located in stop codons and 3'UTR regions of mRNAs. The m6A regulates RNA metabolism, including alternative splicing (AS), alternative polyadenylation (APA), mRNA exportation, decay and stabilization and translation. The metabolic pathway of m6A is regulated by a series of m6A writers, erasers and readers. Recent studies indicate that m6A is essential for the regulation of gene expression, tumor formation, stem cell fate, gametogenesis and animal development. In this systematic review, we summarized the recent advances about the new m6A effector and the effects of m6A on RNA metabolism. Subsequently, we reviewed the function roles of RNA m6A modification in diverse cellular bioprocesses, such as stem cell fate decision, cell reprogramming as well as early embryonic development, and discussed the application potential of m6A modification in regenerative medicine, disease treatment, organ transplantation and animal reproduction.